Effect of Ownership Structure, Investment Opportunity and Debt Policy on Dividend Policy - Nadya Alessya; Abel Tasman (Universitas Negeri Padang, 2022)
The purpose of this study was to analyze the effect of ownership structure, investment opportunities and debt policy on dividend policy in the LQ 45 companies of the Indonesian Stock Exchange in 2017-2020. The population in this study was composed of companies belonging to the LQ 45 group of the Indonesian exchange with a total sample of 30 companies that were consistent in the LQ 45 group of the Indonesian exchange over the period 2017-2020. The analysis technique used is panel data regression using Eviews 9.0. The results of this study indicate that the management of real estate, institutional real estate and investment opportunities have a significant effect on dividend policy, while debt policy has no significant effect on dividend policy..